2011
DOI: 10.2478/s11535-011-0066-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the extracts from fruits of Rumex L. species

Abstract: This study was designed primarily to investigate the antibacterial and antifungal activity of the extracts from fruits of six Rumex L. species: R. acetosa L., R. acetosella L., R. confertus Willd., R. crispus L., R. hydrolapathum Huds. and R. obtusifolius L. The 7 Grampositive and 7 Gram-negative bacteria strains and 5 fungal ones were tested by agar and broth dilution method. Determination of minimal inhibitory concentration (MIC) revealed that the extracts from R. confertus, R. crispus, R. hydrolapathum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 40 publications
(44 reference statements)
3
21
1
1
Order By: Relevance
“…However, in case of P. aeruginosa and C. albicans the MIC values obtained by Wegiera et al [27] were different from our results. In our experiments methanol and acetone extracts of Rumex obtusifolius had 128 μg ml −1 MIC value against P. aeruginosa , whereas its MIC was above the 500 μg ml −1 in the other research [27]. The MIC against C. albicans were above 1024 μg ml −1 in our experiments.…”
Section: Results and Dicussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in case of P. aeruginosa and C. albicans the MIC values obtained by Wegiera et al [27] were different from our results. In our experiments methanol and acetone extracts of Rumex obtusifolius had 128 μg ml −1 MIC value against P. aeruginosa , whereas its MIC was above the 500 μg ml −1 in the other research [27]. The MIC against C. albicans were above 1024 μg ml −1 in our experiments.…”
Section: Results and Dicussioncontrasting
confidence: 99%
“…Wegiera et al [27] showed that ethanol extracts of Rumex confertus seeds had 62.5–125 μg ml −1 MIC values against S. aureus strains which is in coincidence with our data. The results were also similar in case of E. coli .…”
Section: Results and Dicussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The leaf of this plant resembles that of spinach, and the plant is well known for strong acidity in Europe and America, where it is also known as sorrel. The extract of R. acetosa has been reported to have heat-cleaning, diuretic, insecticidal, antimicrobial, and anticancer activities (Lee et al ., 2005; Gescher et al ., 2011; Wegiera et al ., 2011). Decoction of this plant has been used as a folk medicine in Korea to treat arthritis, gastritis and gastric ulcers, and as a substitute for rhubarb, which is an important crude drug for gastrointestinal problems.…”
Section: Introductionmentioning
confidence: 99%
“…수영의 잎은 유럽이나 미국에 존재하는 강한 신맛이 나는 시금치와 비슷하게 생겼으며, sorrel이라 는 이름으로도 알려져 있는 식물이다 [18]. 수영(R. acetosa)의 추출물은 해열, 이뇨, 살충, 항균, 항암활성 등에 효능이 있다고 알려져 있다 [20][21][22]. 또한, 수영을 달인 물은 관절염, 위염, 위궤양 등의 치료에 민간요 법으로 쓰이는 것으로 보고되고 있다.…”
Section: 서 론unclassified